Bringing CSA Practices to Scale: Assessing their contributions to narrow nutrient and yield gaps - Ittersum, Martin K. van; Bussel, Lenny G. J. van; Wolf, Joost; Grassini, Patricio; Wart, Justin van; Guilpart, Nicolas; Claessens, Lieven; Groot, Hugo de; Wiebe, Keith D.; Mason-D'Croz, Daniel; Yang, Haishun; Boogaard, Hendrik L.; et al. (2017)
The Crop Nutrient Gap Project discusses their activities and outputs in this presentation; including a journal article from 2016, Can Sub-Saharan African Feed Itself? The project focuses on supplying different levels of government and the private sector in SSA with different agricultural methods and system that are sensible both from a climate change and food security perspective.